Clostridioides difficile Infection in Patients with Inflammatory Bowel Disease May be Favoured by the Effects of Proinflammatory Cytokines on the Enteroglial Network - Bassotti G; Fruganti A; Maconi G; Marconi P; Fettucciari K (Dove Medical Press, 2021)
Gabrio Bassotti,1,2 Alessandro Fruganti,3 Giovanni Maconi,4 Pierfrancesco Marconi,5 Katia Fettucciari5 1Department of Medicine and Surgery, Gastroenterology, Hepatology & Digestive Endoscopy Section, University of Perugia, Perugia, Italy; 2Gastroenterology & Hepatology Unit, Santa Maria della Misericordia Hospital, Perugia, Italy; 3School of Biosciences and Veterinary Medicine, University of Camerino, Macerata, Italy; 4Department of Biomedical and Clinical Sciences, Gastroenterology Unit, "L. Sacco" Hospital, University of Milano, Milano, Italy; 5Department of Medicine and Surgery, Biosciences & Medical Embryology Section, University of Perugia, Perugia, ItalyCorrespondence: Gabrio BassottiDepartment of Medicine and Surgery, Gastroenterology, Hepatology & Digestive Endoscopy Section, University of Perugia, Perugia, ItalyEmail gabassot@tin.itAbstract: Clostridioides difficile infection is widespread throughout countries and represents an important cause of nosocomial diarrhoea, with relatively high morbidity. This infection often occurs in patients with inflammatory bowel diseases and may complicate their clinical picture. Here, we propose, on the basis of evidence from basic science studies, that in patients affected by inflammatory bowel diseases, this infection might be facilitated by a derangement of the enteric glial cell (EGC) network caused by the effects of proinflammatory cytokines, such as tumour necrosis factor alpha and interferon gamma, which enhance the cytotoxic effects of C. difficile toxin B on EGCs. This hypothesis, if confirmed, could open the door to alternative treatment approaches to fight C. difficile infection.Keywords: Clostridioides difficile infection, cytokines, inflammatory bowel diseases, interferon gamma, tumour necrosis factor alpha